Penentuan Premi Menggunakan Metode Limited Fluctuation Credibility Pada Produk Health Insurance Reasuransi Di Indonesia - Yulita, Tiara; Agus Sofian Eka Hidayat; Gilang Primajati (Griya Journal of Mathematics Education and Application, 2025)
A reinsurance company is a company that provides reinsurance services against the risks faced by the insurance company (the insured). An insured is obliged to pay an amount of money in accordance with the agreement as a form of obligation from the insured for his participation in reinsurance which is called a premium. One method that can be used to determine future premiums based on past experience is limited fluctuation credibility which can predict the value of pure premiums in the future based on current data and insurance manual rates. Using the help of the limited fluctuation credibility method, this study will calculate the estimated value of claim frequency, claim size, aggregate losses and pure health insurance premiums using reinsurance claim experience data. The results of these calculations will be analyzed for differences in value with the value given by reinsurance companies in Indonesia. With this research it is hoped that it can become a standard reference for the credibility of reinsurance companies in determining premiums in the future.